MiR-23a-5p affects postmenopausal osteoporosis by targeting ALX3 to regulate osteoblast differentiation - Honghao Zhang; Wenjun Rao; Rubing Lin; Yingxuan Huang (Journal of Orthopaedic Surgery and Research)
Abstract Background Postmenopausal women are at an increased risk of developing osteoporosis (OP) due to a decline in estrogen levels. This study focuses on miR-23a-5p as the subject of investigation, aiming to elucidate its expression in postmenopausal osteoporosis (PMOP) and to explore its action mechanisms. Methods A cohort of 150 postmenopausal women was recruited for this study, encompassing 78 participants diagnosed with OP and 72 controls without OP. Real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect gene expression levels. OVX rat model was established to simulate clinical features of estrogen deficiency to test the potential role of miR-23a-5p in PMOP. miR-23a-5p overexpression and knockdown MC3T3-E1 cell models were achieved to explore the underlying mechanisms through which miR-23a-5p influence PMOP. Results The expression of miR-23a-5p is upregulated in PMOP and it can distinguish OP patients from non-OP individuals. The expression of miR-23a-5p is related to bone mineral density (BMD) and is a risk factor for PMOP. miR-23a-5p affects serum bone turnover indicators and inhibits osteogenic differentiation marker expression in OVX rats. miR-23a-5p promotes PMOP by negatively regulating the expression of ALX homeobox 3 (ALX3) and affecting the osteogenic differentiation process of MC3T3-E1 cells. Conclusions miR-23a-5p exhibits significantly elevated expression levels in PMOP and it might serve as a promising biomarker. miR-23a-5p plays a pivotal role in the progression of PMOP by negatively regulating ALX3 expression, thereby influencing the osteogenic differentiation process of MC3T3-E1 cells.